Trends in the Intergenerational Transmission of Education among Black South Africans - Prudence Magejo; Miracle Benhura; Tendai Gwatidzo (Institute for the Study of Labor (IZA), 2014)
This paper investigates trends in intergenerational transmission of education among black South Africans changes in correlation between parents' and children's education. Using data for 1954-1993 birth cohorts, we find a decrease in intergenerational transmission of education over the last four decades. The decline is strongest in the lower tail of the educational distribution. Nevertheless, a considerable portion of children's education still depends on family background. Children from poor educational backgrounds face significant barriers to attaining higher levels of education while the reverse applies to those from rich backgrounds. This suggests that initiatives to weaken the intergenerational link, particularly at higher levels of education, should target the offspring of educationally deprived parents.
Keywords: J62; I24; 330; intergenerational transmission; education; South Africa